Combination of Hargreaves method and linear regression as a new method to estimate solar radiation in Perlis, Northern Malaysia - Ismail, Daut, Prof. Dr.; Muhammad Irwanto; Mohd Irwan, Yusoff; Gomesh Nair, Shasidharan; Noor Syafawati, Ahmad (Elsevier Ltd., 2011)
Link to publisher's homepage at http://www.elsevier.com/